Manufacturing of Tinidazole by Recovering and Recycling Catalyst - DONGARE, M.K.; CHANDORKAR, J.G.; RODE, C.V. (Asian Journal of Chemistry, 2010)
In this paper, the recycle process of tungstic acid by recovering it from waste during the manufacture of tinidazole is described. The recovered tungstic acid gives desired quality and quantity of tinidazole.